(untitled) (Journal of Science and Technology Research, 2024)
Total 150 chicken eggs were randomly collected from farms, households, and markets of Rajshahi and Naogaon districts. Isolation and identification of E. coli was done by using cultural and staining characteristics, and biochemical properties. Antibiotic sensitivity assay was also performed for the isolated E. coli by using disc diffusion method. Characterization and detection of antibiotic resistance genes in E. coli isolates were done through PCR analysis. Prevalence of E. coli was 30.00% in chicken eggs in Rajshahi and Naogaon districts. Results of antibiotic sensitivity patterns of the isolated E. coli showed 57.78%, 33.33%, 31.11%, 28.89%, 26.67%, 17.78%, 15.56%, 13.33%, 13.33%, and 11.11% resistance to ciprofloxacin, doxycycline, oxytetracycline, ceftriaxone, amoxycillin, erythromycin, levofloxacin, enrofloxacin, gentamycin, and neomycin, respectively. The isolates also showed 94.44%, 82.22%, 80.00%, 77.78%, 66.67%, 60.00%, 55.56%, 48.89%, 46.67%, and 33.33% sensitive to neomycin, enrofloxacin, erythromycin, levofloxacin, gentamycin, ceftriaxone, oxytetracycline, doxycycline, amoxicillin, and ciprofloxacin, respectively. All 45 phenotypic identified isolates were confirmed as E. coli by PCR analysis. Genotypic identified isolates of E. coli were further characterized by PCR to detect antibiotic resistance genes. Out of 45 E. coli isolates 37 (82.22%) showed tetracycline resistance (tetA) gene, 32 (71.11%) showed tetracycline resistance (tetB) gene, and interestingly all 45 (100%) isolates showed quinolone group resistance (gyrA) gene by PCR analysis. J. of Sci. and Tech. Res. 5(1): 135-142, 2023